A Review of the DTC Controller and Estimation of Stator Resistance in IM Drives - Naveen Goel; Ram Narayan Patel; Saji Chacko (Institute of Advanced Engineering and Science, 2015)
In recent years an advanced control method called direct torque control (DTC) has gained importance due to its capability to produce fast torque control of induction motor. Although in these systems such variables as torque, flux modulus and flux sector are required, resulting DTC structure is particularly simplistic. Conventional DTC does not require any mechanical sensor or current regulator and coordinate transformation is not present, thus reducing the complexity. Fast and good dynamic performances and robustness has made DTC popular and is now used widely in all industrial applications. Despite these advantages it has some disadvantages such as high torque ripple and slow transient response to step changes during start up. Torque ripple in DTC is because of hysteresis controller for stator flux linkage and torque. The ripples can be reduced if the errors of the torque and the flux linkage and the angular region of the flux linkage are subdivided into several smaller subsections. Since the errors are divided into smaller sections different voltage vector is selected for small difference in error, thus a more accurate voltage vector is selected and hence the torque and flux linkage errors are reduced. The stator resistance changes due to change in temperature during the operation of machine. At high speeds, the stator resistance drop is small and can be neglected. At low speeds, this drop becomes dominant. Any change in stator resistance gives wrong estimation of stator flux and consequently of the torque and flux. Therefore, it is necessary to estimate the stator resistance correctly. This paper aims to review some of the control techniques of DTC drives and stator resistance estimation methods.